Conservation of Gayo’s Endemic Orchid (Paphiopedilum primulinum) Through In Vitro Seed Germination and Development with Coconut Water - Tri Mustika Sarjani; Raja Novi Ariska; Ekariana S. Pandia; Dewi Prastika; M. Iqbal H. Tambunan (Jurnal Penelitian Pendidikan IPA, 2023)
Paphiopedilum primulinum is one of endemic orchids in Gayo, Aceh, Indonesia. This terrestrial orchid is registered as endangered species due to IUCN. The low availability of this orchids in nature is due to habitat lost, over-collection for commercial purpose, and low seed germination rate which affected by unidentified factors, yet the study of propagating this orchid is rarely discussed. This experimental research is aim to see the effect of coconut water (CW) concentration to P. primulinum seed germination and development through in vitro culture. The sample of the study used the seed of P. primulinum which age 14 weeks after pollination. The research use ½ Murashige and Skoog media (MS) with four different coconut water (CW) concentration (0,10%, 20%, 30%) and incubated for 90 days. The seed germination rate is calculated due to the percentage of its total germinate seed and seed development indicator divided into 5 stages (0-5). The result shows that the seed of Paphiopedilum primulinum germinate best at 30% CW concentration and only in this concentration the seedling stage reach stage 5 (4.8%). This result implies that 30% CW concentration in ½ MS medium is the best medium to germinate this seed.